2007
DOI: 10.1128/iai.01814-06
|View full text |Cite|
|
Sign up to set email alerts
|

Antigen-Specific CD4+T Cells Recognize Epitopes of Protective Antigen following Vaccination with an Anthrax Vaccine

Abstract: Detection of antigen-specific CD4؉ T cells is facilitated by the use of fluorescently labeled soluble peptidemajor histocompatibility complex (MHC) multimers which mirror the antigen specificity of T-cell receptor recognition. We have used soluble peptide-MHC class II tetramers containing peptides from the protective antigen (PA) of Bacillus anthracis to detect circulating T cells in peripheral blood of subjects vaccinated with an anthrax vaccine. PA-specific HLA class II-restricted T lymphocytes were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…The reasons for the delay between completion of the priming series and attainment of maximum responses are unknown. The sustained presence of PAspecific IFN-␥ (Th1)-and IL-4 (Th2)-secreting cells, together with the sustained SI, indicated that the 3-IM series provided effective immunological priming and stimulated a mixed Th1/Th2 response in NHPs, in agreement with the observations of Laughlin and coworkers for AVA in humans (19). CD4 ϩ T cells contribute to activation of naïve B cells to produce clones of germinal center-located, activated B cells and to produce memory B cells and long-lived plasma cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The reasons for the delay between completion of the priming series and attainment of maximum responses are unknown. The sustained presence of PAspecific IFN-␥ (Th1)-and IL-4 (Th2)-secreting cells, together with the sustained SI, indicated that the 3-IM series provided effective immunological priming and stimulated a mixed Th1/Th2 response in NHPs, in agreement with the observations of Laughlin and coworkers for AVA in humans (19). CD4 ϩ T cells contribute to activation of naïve B cells to produce clones of germinal center-located, activated B cells and to produce memory B cells and long-lived plasma cells.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies in humans showed that AVA stimulated the production of CD4 ϩ T cells that recognized multiple epitopes within PA and that these responses were detected in vaccinated and, surprisingly, also in nonvaccinated subjects (18,19). The frequencies of PA-specific T cells were higher in vaccinees than in nonvaccinees.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, antibody responses to PA after vaccination are T-helper (Th) dependent [40] and PA peptides are presented by infected macrophages [43], suggesting that the epitope-specific T cells may be required for mounting a protective immune response.…”
Section: Functional Characteristics Of B Anthracis Epitopesmentioning
confidence: 99%
“…Domains 3 and 4 contain murine T-cell epitopes [41][42][43], while single human T-cell epitopes have been described in domains 1 and 2 [40]. Interestingly, the domain-1 epitopes described for PA-immunized mice and a vaccinated human are located within the PA20 region that is cleaved before heptamerization [19], suggesting that this region is still processed for presentation on MHC class II molecules after vaccination, allowing the immune system to respond to the entire PA83 molecule and not just the active PA63.…”
Section: Localization Of B Anthracis Pa Epitopesmentioning
confidence: 99%